2015
DOI: 10.1039/c4ra14559c
|View full text |Cite
|
Sign up to set email alerts
|

Green catalysis by nanoparticulate catalysts developed for flow processing? Case study of glucose hydrogenation

Abstract: Heterogeneous catalysis, flow chemistry, continuous processing, green solvents, catalyst immobilization and recycling are some of the most relevant, emerging key technologies to achieve green synthesis. However, a quantification of potential effects on a case to case level is required to provide a profound answer, whether they can lead to a superior process compared to the industrial standard. To do so, holistic environmental assessment approaches are very useful tools providing insights and decision support d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In the recent years, an increased attention has been paid to for the synthesis of fine chemicals in continuous mode. Under such conditions, a compromise should be made between a pressure drop, favorable at large sizes of catalysts, and mass-transfer limitations. Catalyst deactivation as well as product distribution can be different from those obtained under kinetic regime with fine catalyst powders.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, an increased attention has been paid to for the synthesis of fine chemicals in continuous mode. Under such conditions, a compromise should be made between a pressure drop, favorable at large sizes of catalysts, and mass-transfer limitations. Catalyst deactivation as well as product distribution can be different from those obtained under kinetic regime with fine catalyst powders.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the lower catalytic activity of nickel as compared to other precious-metal-based conventional hydrogenation catalysts, such as ruthenium, results in the need for high hydrogen pressure and harsh operating conditions. Consequently, a significant energy demand must be satisfied compared to that required when using more active hydrogenation catalysts and, thus, higher environmental impacts are associated with the use of Raney nickel catalysts [24].…”
Section: Featured Application: Catalytic Transfer Hydrogenation From mentioning
confidence: 99%
“…Nevertheless, the lower catalytic activity of nickel as compared to other precious-metal-based conventional hydrogenation catalysts, such as ruthenium, results in the need for high hydrogen pressure and harsh operating conditions. Consequently, a significant energy demand must be satisfied compared to that required when using more active hydrogenation catalysts and, thus, higher environmental impacts are associated with the use of Raney nickel catalysts [24].This work focuses on gaining insights into a developing alternative reaction pathway to the conventional hydrogenation procedure used to transform glucose into sorbitol by exploring the feasibility of carrying out the transformation through catalytic transfer hydrogenation (CTH) using a hydrogen donor. CTH is, a priori, a more sustainable alternative to conventional hydrogenation with molecular hydrogen because of the lower requirements for high-pressure conditions.…”
mentioning
confidence: 99%
“…Flow hydrogenation is particularly useful in the reduction in alkene and alkyne bonds as is evident from the examples shown in Table 2. Gericke et al developed ruthenium-nitrogendoped carbon nanotubes (NCNT) and ruthenium-hyperbranched polystyrene-supported (HPS) catalysts, providing a more sustainable process [24]. Gericke et al suggested that HPSand NCNT-supported catalysts are a suitable alternative to Raney Ni and have an increased production rate per mole of catalyst compared to Raney Ni.…”
Section: Alkene Reductionsmentioning
confidence: 99%